21st Century Anthropology Scholarship: A Citation Analysis. Issue 3 (3rd July 2017) - Seaman, Priscilla; Kaczor, Sue A.
Abstract: A 2017 citation study looked at four scholarly anthropology journals in order to evaluate current research trends. This study examined the following journals: Current Anthropology, the American Anthropologist, the American Ethnologist, and the Journal of Anthropological Research . The results showed an average of 89.9 citations per article, which is a large increase over previous studies. The breakdown by the largest two categories showed 48.1% citations to total books, compared to 41.2% for scholarly journals. All other source types of citations comprised only 10.7% of total citations. These results were compared to a 2005 study by William Robinson and Paul Posten of the same four journals from 1999.